MANAJEMEN PEMANENAN KELAPA SAWIT TANAMAN MENGHASILKAN PADA PERKEBUNAN SENAGAN PT. SOCFINDO AFDELING II - Keumala Fadhiela ND; Fery Firnanda (Agros Journal of Agriculture Science, 2023)
ABSTRACTThis study aims to determine the technical management of oil palm harvesters, management, and analysis of the production produced in the oil palm plantation of PT. Socfindo, Seunagan plantation, Afdeling II, Nagan Raya August-November 2022. Data collection in this study was carried out by collecting primary data and secondary data. primary data collection was obtained through direct observation in the field, discussions and interviews with employees, foremen and assistants of section II. Secondary data was obtained from existing data in the plantation including the geographical location of the plantation, climatic conditions, area size and land use, production and productivity, company organizational structure, and company regulations or standard norms. The results showed that the management of oil palm harvesting at the Seunagan Afdeling II Plantation was going quite well, the harvest criteria applied to normal fruit or fruit bunches that were categorized as ripe (harvestable) which was marked by the release of loose fruit from the bunches of <4 loose fruit. per bunch. Harvest rotations are applied 7-8 days between two harvests per block. the percentage of normal fruit is 98.6% indicating that the quality of the fruit harvested is classified as very good for fruit according to what is applied by the company, where the condition for fruit quality must be ≥98%. As well as the percentage of rotten fruit and unripe fruit respectively 0.8% and 0.7%. For the application of the premium, if the harvester harvest exceeds the service base, namely 40 degrees,. If the harvester is able to harvest more than the length basis, the harvester is entitled to receive a premium of Rp. 905. Meanwhile, the foreman's premium depends on the employee's income multiplied by 12%, while the premium for fruit crates is multiplied by 11%.